Assess the level of coping strategies adopted by care givers of differently abled child in selected Paediatric OPD’s of hospitals in Pune city - Dr. Mrs. Bhagyashree Jogdeo, Monal Kurane,Sneha Sankpal-Desai, Kanchan Shinde, Sharmila Kulal, Rucha Bade (South Eastern European Journal of Public Health, 2025)
Introduction: Intellectual impairment, cerebral palsy, autism spectrum disorder, epilepsy, and other conditions are referred to as development disabilities. The term used to describe the bulk of childhood impairments is developmental abnormalities, or any physical or psychological illness that may prevent a child from developing cognitively, physically, or emotionally in relation to other children. The arrival of a disabled child may have an effect on every aspect of the family relations. It entails re-evaluating how well the household is operating.1 Tital of study: “Assess the level of coping strategies adopted by care givers of differently abled child in selected Paediatric OPD’s of hospitals in Pune city. Material and Methods: Quantitative approch with exploratory research design. It was carried out on 100 samples. The non-probability purposive sampling technique was used to select samples. Result: Findings showed that the frequency & percentage distribution . Majority 81% were having poor coping strategies, 19% were having good coping strategies and no one having very poor & very good coping strategies adopted by care givers of differently abled child with mean of 75.4 with S.D of + 7.08. Conclusion: Study concluded that the information demonstrates the relationship between carers' coping mechanisms and their degree of stress and r value is 0.0399. Although there is a formal negative correlation, there is only a weak association between the variables (The nearer value is to zero, the weaker the relationship). As a result, there is no connection between carers' coping mechanisms and their degree of stress.